αCaMKII and PSD-95 differentially regulate synaptic expression of NR2A and NR2B-containing NMDA receptors in hippocampus - Park, C. Sehwan (2007)
NMDA receptors (NMDARs) are critical determinants of bidirectional synaptic plasticity, however, studies of NMDAR function have been based primarily on pharmacological and electrophysiological manipulations, and it is still debated whether there are subunit-selective forms of long-term potentiation (LTP) and long-term depression (LTD). Here we provide ultrastructural analyses of axospinous synapses in CA1 stratum radiatum of transgenic mice with mutations to two key underlying postsynaptic density (PSD) proteins, PSD-95 and αCaMKII. Distribution profiles of synaptic proteins in these mice reveal very different patterns of subunit-specific NMDAR localization, which may be related to the divergent phenotypes of the two mutants. In PSD-95 PDZ3 truncated mice in which LTD could not be induced but LTP was found to be enhanced, we found a subtle, yet preferential displacement of synaptic NR2B subunits in lateral regions of the synapse without affecting changes in the localization of NR2A subunits. In persistent inhibitory αCaMKII T305D mutant mice with severely impaired LTP but stable LTD expression, we found a selective reduction of NR2A subunits at both the synapse and throughout the cytoplasm of the spine without any effect on the NR2B subunit. In an experiment of mutual exclusivity, neither PSD-95 nor αCaMKII localization was found to be affected by mutations to the corresponding PSD protein suggesting that they are functionally independent of the other in the regulation of NR2A and NR2B-containing NMDARs preceding synaptic activity. Consequently, there may exist at least two distinct PSD-95 and αCaMKII-specific NMDAR complexes involved in mediating LTP and LTD through opposing signal transduction pathways in synapses of the hippocampus. The contrasting phenotypes of the PSD-95 and αCaMKII mutant mice further establish the prospect of an independent and, possibly, competing mechanism for the regulation of NMDAR-dependent bidirectional synaptic plasticity.